2020
DOI: 10.3390/ijms21072399
|View full text |Cite
|
Sign up to set email alerts
|

Programmed Cell Death-1: Programmed Cell Death-Ligand 1 Interaction Protects Human Cardiomyocytes Against T-Cell Mediated Inflammation and Apoptosis Response In Vitro

Abstract: Aim: Immunological checkpoint therapy is considered a powerful method for cancer therapy and acts by re-activating autologous T cells to kill the cancer cell. Myocarditis cases have been reported in cancer patients after immunological therapy; for example, nivolumab treatment is a monoclonal antibody that blocks programmed cell death-1/programmed cell death ligand-1 ligand interaction. This project provided insight into the inflammatory response as a benchmark to investigate the potential cardiotoxic effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 30 publications
(32 reference statements)
6
31
0
Order By: Relevance
“…Expression of the inflammatory transcription factors NLRP3, MyD88, and p65/NF-κB are also increased in cardiomyocytes after ICI treatment [30]. Further proving this point, anti-PD-1-treated mice had more CD4+ and CD8+ T cell infiltration in the heart as compared to a control group [29]. However, it is unclear exactly what the T cells are targeting.…”
Section: Generalmentioning
confidence: 85%
See 2 more Smart Citations
“…Expression of the inflammatory transcription factors NLRP3, MyD88, and p65/NF-κB are also increased in cardiomyocytes after ICI treatment [30]. Further proving this point, anti-PD-1-treated mice had more CD4+ and CD8+ T cell infiltration in the heart as compared to a control group [29]. However, it is unclear exactly what the T cells are targeting.…”
Section: Generalmentioning
confidence: 85%
“…Love et al found in a similar study that CTLA-4 removal on T cells also caused severe myocarditis in mice, but lack of IL-12 prevented CD8+ T cells from proliferating, thus ameliorating the myocarditis [32]. PD-L1 expressed in the human myocardium is involved in protecting immune-mediated cardiac injury and inflammation [29].…”
Section: Generalmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of cardiovascular complications seen upon PD-1/PD-L1 and combination therapy was much higher as opposed to CTLA-4 therapy. 8,53 Furthermore, Tay et al 54 provided insights into cardiomyopathy resulting from PD-1-PD-L1 axis blockade, by using nivolumab in vitro in Rockefeller University embryonic stem cells (RUES)derived cardiomyocytes and in vivo in melanoma tumorbearing mice. They observed cardiomyocyte inflammation and apoptosis along with an increased expression of cardiac TnI and left ventricular dilatation.…”
Section: Serial Troponin Determination During Ici Therapymentioning
confidence: 99%
“…They observed cardiomyocyte inflammation and apoptosis along with an increased expression of cardiac TnI and left ventricular dilatation. 54 Thus, elevated troponin levels might indicate low-grade or scattered myocardial inflammation as a result of blocking the PD-1–PD-L1 axis which might not yet be visual on cardiac imaging. 55 , 56 The best technique to diagnose subclinical cardiac dysfunction has not yet been established.…”
Section: Introductionmentioning
confidence: 99%